Essential nutrients and cerebral small vessel diseases: a two-sample Mendelian randomization study - Li, Jiayi; Xia, Kailin; Wang, Zhengrui; Liu, Yanru; Tong, Yicheng; Wang, Yuwei; Zhou, Yumou; Zhang, Linjing; Tang, Lu; Fan, Dongsheng; Yang, Qiong (Frontiers in Nutrition, 2023)
Background Previous studies have suggested a potential association between nutrients and cerebral small vessel disease (CSVD), but this association has not been fully addressed. Object We intended to clarify the causal associations between four categories of essential nutrients (amino acids, polyunsaturated fatty acids, minerals and vitamins) and two acute manifestations of CSVD (intracerebral hemorrhage and small vessel stroke) using two-sample Mendelian randomization (MR) analysis. Method We obtained European-based large-scale genome-wide association studies (GWASs) related to CSVD (6,255 cases and 233,058 controls) and nutrient concentrations. Causality evaluation mainly included the results of the inverse variance-weighted (IVW) method. The simple median method, the weighted median method and the MR–Egger method were adopted for sensitivity analyses. Results For ICH or SVS, increased levels of phenylalanine (OR = 1.188, p < 0.001) and dihomo-gamma-linolenic acid (DGLA) (OR = 1.153, p = 0.001) showed risk effects, while docosapentaenoic acid (DPA) (OR = 0.501, p < 0.001), zinc (OR = 0.919, p < 0.001), and arachidonic acid (OR = 0.966, p = 0.007) showed protective effects. For lobar hemorrhage or SVS, AA (OR = 0.978, p < 0.001), zinc (OR = 0.918, p < 0.001), and retinol (OR = 0.753, p < 0.001) showed risk effects; DPA (OR = 0.682, p = 0.022), gamma-linolenic acid (OR = 0.120, p = 0.033) and 25(OH)D (OR = 0.874, p = 0.040) showed protective effects. For nonlobar hemorrhage or SVS, DGLA (OR = 1.088, p < 0.001) and phenylalanine (OR = 1.175, p = 0.001) showed risk effects. Conclusion Our study analyzed the effect of nutrients on CSVD risk from a genetic perspective, with implications for CSVD prevention through nutrient supplementation.